Pengaruh Return on Assets (ROA) dan Debt to Equity Ratio (DER) terhadap Harga Saham Pada PT Astra Agro Lestari Tbk (AALI) Periode 10-15 Tahun Terakhir - Hairunisa, Urwatun; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the associative effect of Return on Assets (ROA) and Debt to Equity Ratio (DER) on the stock price of PT Astra Agro Lestari Tbk (AALI) over the past 10 years (2014-2023). This research uses a quantitative associative method with secondary data obtained from the Indonesia Stock Exchange (IDX). To ensure robust statistical analysis, quarterly financial data was utilized, resulting in 40 observation points as the research sample. Data analysis techniques include classical assumption tests, multiple linear regression, t-test, F-test, and the coefficient of determination using statistical software. The results show that partially, Return on Assets (ROA) has a significant positive effect on the stock price, indicating that higher profitability increases investor trust and stock value. Conversely, Debt to Equity Ratio (DER) has a significant negative effect on the stock price, implying that higher leverage increases financial risk perceptions, thus lowering stock prices. Simultaneously, both ROA and DER significantly influence the stock price of PT Astra Agro Lestari Tbk. The implication of this study suggests that investors should monitor profitability and solvency ratios, while management should optimize asset utilization and maintain prudent debt levels.